Particular algorithm of ordering Uolsha basis functions - Белецкий, А. Я.; Клобуков, В. В. (Proceedings of National Aviation University, 1999)
Considered is one of the algorithms of ordering Uolsha basis functions which permits (taking into account phase characteristics of spector) to determite the single-valued correspondence of frequences at the processor input and output Fourier fast transformation